Liposome-Encapsulated Baicalein Suppressed Lipogenesis and Extracellular Matrix Formation in Hs68 Human Dermal Fibroblasts - Fang, Chien-Liang; Wang, Yiwei; Tsai, Kevin H.-Y.; Chang, Hsin-I (Frontiers in Pharmacology, 2018)
The dermis of human skin contains large numbers of fibroblasts that are responsible for the production of the extracellular matrix (ECM) that supporting skin integrity, elasticity and wound healing. Previously, an in vivo study demonstrated that dermal fibroblasts siting in the lower dermis are capable to convert into skin adipose layer and hence fibroblast lipogenesis may vary the structure and elasticity of dermis. In the present study, Hs68 human dermal fibroblasts were utilized as an in vitro model to study the lipogenesis via using adipogenic differentiation medium (ADM). Baicalein, isolated from Scutellaria baicaleinsis, is one of the flavonoids to inhibit adipocyte differentiation due to high antioxidant activity in vitro. In order to develop a suitable formulation for baicalein (a poorly water-soluble drug), soybean phosphatidylcholine (SPC) was used to prepare baicalein-loaded liposomes to enhance drug bioavailability. Our results demonstrated that liposome-encapsulated baicalein protected cell viability and increased cellular uptake efficiency of Hs68 fibroblasts. Lipid accumulation, triglyceride synthesis and gene expressions of lipogenesis enzymes (FABP4 and LPL) were significantly increased in ADM-stimulated Hs68 fibroblasts but subsequently suppressed by liposome-encapsulated baicalein. In addition, ADM-induced TNF-α expression and related inflammatory factors was down-regulated by liposome-encapsulated baicalein. Through ADM-induced lipogenesis, the protein expression of elastin, type I and type III collagens increased remarkably, whereas liposome-encapsulated baicalein can down-regulate ADM-induced ECM protein synthesis. Taken together, we found that liposome-encapsulated baicalein can inhibit ADM-induced lipid accumulation and ECM formation in Hs68 fibroblasts through the suppression of lipogenesis enzymes and inflammatory responses. Liposome-encapsulated baicalein may have the potential to improve wound healing and restore skin structure after skin injury.